THE INFLUENCE OF LEADERSHIP EMOTIONAL INTELLIGENCE AND COMMITMENT OF SCHOOL ORGANIZATION ON SELF EFFICACY - Laksmitha Putri SETIADY (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2019)
The aim of this research was to reveal the influence of Leadership Emotional Intelligence (x1) and Commitment of School Organization (x2) on Teacher Self Efficacy (x3). Hypotheses tested: (1) there is a direct and positive influence of Leadership Emotional Intelligence on Teacher Self Efficacy, (2) there is a direct and positive influence of Commitment of School Organization on Teacher Self Efficacy, (3) there is a direct and positive influence of Leadership Emotional Intelligence on Commitment of School Organization. Applying Slovin Formula, 109 teachers were proportionally and randomly surveyed out of population 151 teachers. The researcher used validated and reliable questionnaires for collecting data. Croanbach’s reliability tested Likert Scales. Statistical requirements for analyses were fulfilled using test of normality (Liliefors), test of linearity and test of homogeneity. In this study the researcher used simple regression and path analyses and found that Leadership Emotional Intelligence and Commitment of School Organization have direct and positive influence on Teacher Self Efficacy.